Nuclear deformation by microtubule molecular motors - Naruemon Rueangkham; Miguel Valle-Incln Cabello; Franziska Lautenschlger; Rhoda J Hawkins (My University, 2025)
We present a model to calculate the displacement and extension of deformable cellular cargo pulled by molecular motors stepping along cytoskeletal filaments. We consider the case of a single type of molecular motor and cytoskeletal filaments oriented in one dimension in opposite directions on either side of a cargo. We model a deformable cargo as a simple elastic spring. We simulate this tug-of-war simple exclusion process model using a Monte Carlo Gillespie algorithm and calculate the displacement and extension of the cargo for different configurations of motors and filaments. We apply our model to kinesin-1 motors on microtubules to investigate whether they are strong enough to translocate and deform the largest cellular cargo, the nucleus. We show that the extension caused by motors on a single microtubule saturates for larger numbers of motors but that the extension and displacement scales linearly with the number of microtubules. We also show how the binding and unbinding behaviors of molecular motors on microtubule filaments affect the nuclear deformation. Our modelling results correspond to experiments on cells treated with the drug kinesore, which is thought to increase rescue events resulting in more stable microtubules and more active kinesin-1 molecular motors bound to them. Both the experiments and our simulations result in nuclear deformation.
Keywords: Kinesin; Molecular motor; Microtubule and mitosis dynamics